Study on the storage stability of swamp taro (Cyrtosperma merkusii (Hask) Schott) all-purpose premix sauce. - Bolivar, Joesel Mae Nunez (2018.)
The storage stability of all-purpose taro (APT) premix sauce packed in polypropylene (PP) and low density polyethylene (LDPE) at room temperature (28°-33°C) was determined. Moisture content and water activity of APT premix sauce packed in PP and LDPE increased with storage time. pH of the APT premix sauce on the other hand, showed fluctuating values. The flowability of the APT premix sauce cecreased with storage days. Microbial count of the yeast and molds were less than 10 or below the countable number of colonies. The APT premix sauce sensory attributes were evaluated by fifteen (15) well-oriented Food Technology students using the 15-cm line scale. Same panelists evaluated the APT premix sauce until the end of the study. There wasno significant difference in the sensorial attibutes of the APT premix sauce. Twenty-seven (27) grams of APT premix sauce was reconstituted with 235 mL of water. The APT sauce was subjected to descriptive and general acceptability test. There was no significant change in the sensorial attributes of the APT sauce. The panelists preferred the APT sauce packed in PP. The APT premix sauce was still stable at day 35 and PP was shown to be a better packaging material than LDPE.
Thesis - B.S. (Food Technology) - School of Technology, University of the Philippines Visayas.
Keywords: Swamp taro; Cyrtosperma merkusii (Hask) Schott; Condiment; Palauan